Apheresis for the treatment of relapses in MS and NMOSD: reduced antibody reactivities, gene expression changes and potential clinical response indicators - Hecker, Michael; Fitzner, Brit; Ludwig-Portugall, Isis; Bohne, Friederike; Heyland, Edmar; Klehmet, Juliane; Grothe, Matthias; Schwab, Matthias; Winkelmann, Alexander; Meister, Stefanie; Dudesek, Ales; Wurm, Hannah; et al. (Frontiers in Immunology, 2025)
BackgroundHigh-dose glucocorticoids are the standard treatment for acute relapses in patients with multiple sclerosis (MS) or neuromyelitis optica spectrum disorder (NMOSD). Therapeutic apheresis can be considered for the escalation of relapse therapy, but some patients still do not recover sufficiently. We aimed to explore the effects of apheresis on humoral and cellular immune parameters and to identify features that correlate with beneficial clinical outcomes.MethodsWe studied two cohorts comprising a total of 63 patients with MS or NMOSD who were undergoing relapse therapy with either methylprednisolone or apheresis. Blood samples were collected immediately before and after therapy to isolate plasma or serum as well as immune cells. We then measured (1) concentrations of the immunoglobulin isotypes IgG, IgM and IgA, (2) antibody reactivities against 12 peptides derived from potential autoantigens and Epstein-Barr virus proteins, (3) frequencies of CD19+ B cells, CD3+ T cells and CD14+ monocytes, (4) transcriptome profiles of CD19+ B cells and CD4+ T cells and (5) mRNA levels of 7 cytotoxicity-related genes in CD4+ T cells. The data were compared with regard to changes under therapy and with regard to differences between clinical responders and non-responders.ResultsThe initial therapy with methylprednisolone had no significant effect on immunoglobulin levels and (auto)antibody reactivities (nmax=27 MS patients). In contrast, MS patients who underwent apheresis (nmax=27) showed strong immunoglobulin reduction rates, especially for IgG, and decreased antibody reactivities against all tested peptides. EBNA1 (amino acids 391-410) was the only peptide that also reached the significance level in NMOSD patients (n=9). Non-responders to apheresis (n=12) had on average higher anti-EBNA1 (391-410) reactivities than responders (n=24) at baseline. Apheresis also led to a decrease in the proportion of monocytes, an increase in the proportion of T cells (n=29 patients with MS or NMOSD) and moderate transcriptome changes (nmax=4 MS patients). A gene expression signature that is characteristic of CD4+ cytotoxic T lymphocytes (CD4-CTLs) was found to be elevated at baseline in non-responders to apheresis, although this could not be validated with statistical significance (n=19 MS patients).ConclusionOur data reveal that therapeutic apheresis in MS rapidly leads to a significant decrease in IgG reactivities against EBNA1 (391-410) and cross-reactive targets such as GlialCAM (370-389) and also has an impact on the gene expression of B cells and T cells. Further studies are required to verify whether anti-EBNA1 (391-410) antibody reactivities and the expression of CD4-CTL-related genes may be indicative of the individual clinical response to this therapy.